Women SOS Safety App - Saravanan, Youvadarshan; Marjudi, Suziyanti (Applied Information Technology And Computer Science, 2024)
Emergency response can benefit from smartphone apps for portable devices. One such tool is GPS technology, which, in addition to enabling communication, can also be used to locate rescuers by signaling their location. In an emergency, the user may press the emergency alert button to instantly email an emergency pre-programmed message to emergency contacts along with the user’s current GPS position. The purpose of this project is to develop a smartphone application for locating, identifying, and alerting victims’ whereabouts. The Women SOS Safety App was developed using the System Development Life Cycle (SDLC) waterfall approach. The app was built using this suggested methodology because the requirements for the app were well-defined and the timeline for development was tight. This app is to support users who are in immediate need of assistance and to keep them in touch with their loved ones by instantaneously sending a photo, GPS information, and other details at critical times. In conclusion, utilizing this app will offer the quickest and most straightforward method of seeking assistance in an emergency.